The Association of Clinical Competence and Emotional Intelligence with Life Satisfaction in Nurses: The Mediating Role of Job Satisfaction - Abbaszadeh, Zeinab; Bakhtiarpour, Saeed; Safarzadeh, Sahar; Asgari, Parviz; Heidari, Alireza (Advances in Nursing & Midwifery, 2024)
Introduction: Nurses are pivotal to the healthcare system, providing essential care to patients. However, the nursing profession is characterized by demanding workloads and significant challenges. Accordingly, this study aimed to predict life satisfaction based on clinical competence and emotional intelligence through job satisfaction in nurses working in hospitals and medical centers in Ahvaz in 2023. Methods: The present study was correlational and of the structural equation modeling type. The study population included all nurses working in Ahvaz City hospitals during the period of April to June 2023. A convenience sample of 182 nurses was selected for participation. The research tools included the Satisfaction with Life Scale (SWLS), Minnesota Satisfaction Questionnaire (MSQ), and Competency Inventory for Registered Nurses (CIRN), and Emotional Intelligence Scale (EIS). Data were analyzed using structural equation modeling (SEM) with SPSS-25 and AMOS-24 software. All hypotheses were tested at a significance level of α = 0.05. Results: The results showed that there was a positive and significant relationship between clinical competence and job satisfaction in nurses (P<0.001). The relationship between emotional intelligence and job satisfaction in nurses was also positive and significant (P<0.001). In addition, the relationship between job satisfaction and life satisfaction was positive and significant (P<0.001). The results suggest that job satisfaction mediates the relationship between emotional intelligence and clinical competence with life satisfaction in nurses (P<0.001). Conclusions: The findings of this study indicate positive and significant associations between clinical competence, emotional intelligence, and life satisfaction among nurses. Moreover, job satisfaction emerged as a mediating factor, suggesting that nurses with higher levels of clinical competence and emotional intelligence report greater job satisfaction, which subsequently contributes to increased life satisfaction. These results underscore the importance of fostering both clinical skills and emotional intelligence in nurses to enhance their overall well-being and potentially optimize patient care outcomes.